Foto documental sobre las Danzas Urbanas Locking y Wacking en Lima - Toledo Cieza, Piero Eduardo (2020)
Among the varied range of urban dances in Lima, Locking and Wacking are some of the least known. This documentary photo diffuses through various photographs such as the dancers develop in their different contexts within Lima, and as despite economic difficulties, they manage to take advantage of their abilities. Through a follow-up, the dancer is made visible as the creator of his own semiosphere on the street along with his community of dancers. Because in the words of the dancer 90s "Doctor Dance": "this has not been documented before, there is no record on the internet nor anywhere ”. The Photo Book of this project can be viewed at this link: https://bit.ly/32fwEEJ